Are Impulsive Adolescents Differentially Vulnerable to Normative or Situational Peer Influences? A Partial Replication Study - De Buck, Ann (Journal of contemporary criminal justice, 2019)
Ample research in criminology investigates the role of deviant peers in the development of adolescent offending. Different theoretical explanations account for distinct peer influences. The socialization perspective argues that deviant peers influence behavior through the provision of norms and values, whereas the situational perspective argues that deviant peers provide situational opportunities for deviant behavior. This study partially retests the propositions put forward by Thomas and McGloin’s study of dual systems, differential peer effects, and adolescent offending. We address the question to what extent trait impulsivity affects social and situational peer processes controlling for parental supervision, family bond, school bond, and deviant norms. Analysis of the cross-national International Self-Report Delinquency Study (ISRD3) data suggests that adolescents at the edges of trait impulsivity are differentially vulnerable to the effects of deviant peer processes. However, the findings need to be nuanced. We discuss the contribution of the current study to a better understanding of the interplay between individual characteristics and exposure to deviant peers.